2005
DOI: 10.1002/pssb.200541085
|View full text |Cite
|
Sign up to set email alerts
|

On the magnetic compensation effect of lithium‐chromium ferrites Li0.5CrxFe2.5–xO4 (0 ≤ x ≤ 1.55)

Abstract: Lithium-chromium ferrites Li 0.5 Fe 2.5-x Cr x O 4 (0 ≤ x ≤ 1.55) were studied using X-ray diffraction, magnetization measurements and Mössbauer spectroscopy. X-ray diffraction patterns show that all samples have cubic spinel structure. The temperature dependent magnetic measurements revealed that a magnetic compensation point appears at chromium concentration x = 1.05, 1.25 and 1.55. Moreover, it was observed that the Curie temperature T C decreases and approaches the compensation temperature T K as Cr 3+ sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…This is consistent with the decrease of the lattice constant a, as shown in Table 2, with iron substitution by chromium which could be interpreted as due to bigger size effect of Fe3+ (0.67 Å) than Cr3+ (0.64 Å). This has already been discussed in a previous publication on Mg-Cr ferrites [20] and similar behavior has been reported for mixed structure spinel Ni-Cr ferrites [24] as well as Ni-Al ferrites [26].…”
Section: Rietveld Refined Xrd Pattern Of Mgfe2o4supporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with the decrease of the lattice constant a, as shown in Table 2, with iron substitution by chromium which could be interpreted as due to bigger size effect of Fe3+ (0.67 Å) than Cr3+ (0.64 Å). This has already been discussed in a previous publication on Mg-Cr ferrites [20] and similar behavior has been reported for mixed structure spinel Ni-Cr ferrites [24] as well as Ni-Al ferrites [26].…”
Section: Rietveld Refined Xrd Pattern Of Mgfe2o4supporting
confidence: 88%
“…Subsequently, understanding thoroughly how magnetic properties of these ferrites are linked with the cationic distribution would enable to fine-tune these properties by regulating the distribution. It is well known that chromium substitutions in any spinel ferrites have preference to octahedral sites only [23,24]. So, in the case of magnesium ferrites, choosing chromium for doping would yield to lowering the degree of inversion δ and, hence, varying the net magnetic moment of this system in one way or the other.…”
Section: Introductionmentioning
confidence: 99%
“…These are ferrimagnetic materials in which the various temperature-dependent magnetizations of the spin-up and spin-down sublattices cross over at temperatures below the Curie temperature, resulting in a change of sign of the net spontaneous magnetization at that temperature. In a previous paper [9], we agreed with Kuznetsov et al [10] that Li 0.5 Fe 2.5-x Cr x O 4 ferrites have a completely inverted spinel structure for concentrations up to x = 1.25.…”
Section: Introductionsupporting
confidence: 87%
“…The changes in the inter-and intrasublattice interactions depends on the electronic configuration of Cr 3+ ion and the change in interaction angles and lengths between magnetic ions in the crystal lattice due to Cr substitution. The decrease of intersublattice interaction N AB is responsible for the decrease of Curie temperature, a tendency which had been observed in other Cr substituted ferrite systems such as Fe 3−x Cr x O 4 [9] and LiFe 2.5−x Cr x O 4 [11]. Recent studies have shown that the magnitude of the exchange coupling between Cr ions J BB Cr−Cr in chromite compounds [22], [23] is much larger than those between Ni and Fe ions [24] at B sites of nickel ferrite J BB i j (i , j = Ni or Fe).…”
Section: Methodsmentioning
confidence: 59%